MARX’S VAMPIRE IN VAMPIRE LITERATURE. A MARXIST ANALYSIS ON STOKER’S DRACULA, MARTIN’S FEVRE DREAM AND DEL TORO’S THE STRAIN TRILOGY - Nikodemus Yudho Sulistyo (Jurnal Ilmiah Spectral, 2019)
There is a parallel relationship research between vampire literature and Marx’s works on the theory of social class and struggle as what so called as Marx’s Vampire. The obvious connection of the fictitious characters of vampires who suck blood of the victims lies on the analogy of the capitalists as the superior beings suck the workforce of the working class labours. Through the three novels, one title is in the form of trilogy, Bram Stoker’s Dracula, George R. R. Martin’s Fevre Dream, and Guillermo del Toro and Chuck Hogan’s The Strain Trilogy, the writer found out that the vampires in the novels are portrayed as masters who literally suck the blood from the victims, the slaves, or those who have the characteristics of being ones. The master and slave relationship describes the theory of Marx’s Vampire